Micrococcus yunnanensis and Psychrobacter sp. as Potential Producers of Polymers from Hot Spring - Jabeen, Asma; Batool, Rida; Jamil, Nazia (Department of Agro-industrial Technology, University of Brawijaya, 2022)
AbstractPolyhydroxyalkanoates (PHAs) and exopolysaccharides (EPSs) are biopolymers bacteria under nutrient-limiting conditions. In this study, bacterial strains were isolated from hot springs. Soil samples were collected from Tatta Pani, Azad Kashmir, Pakistan. Bacterial strains AJ2 and AJ3 were selected due to their ability to produce PHAs and EPSs. Phylogenetic analysis showed that strain AJ2 was Micrococcus yunnanensis and AJ3 was Psychrobacter sp. Three carbon sources (glucose, glycerol, and molasses) were used for polymer production. The effect of high pH (8) and high temperature (55 °C) was checked on PHAs and EPSs production. The highest yield of PHAs was given by strain AJ3 (89.43%) with molasses. When grown at 55 °C for 24 hours, strain AJ3 showed the highest PHAs accumulation, 79% with glucose. At alkaline pH 8, strain AJ3 gave 34% PHAs with molasses. The highest EPSs production was observed for strain AJ3. AJ3 gave 70g/L of EPSs with both glucose and glycerol. The amplification of the phaC gene was done to confirm the genetic basis of PHAs production. FTIR analysis showed clear bands at 1722 cm-1 and 2925 cm-1 representing the carbonyl and alkyl groups of PHAs, respectively.Keywords: exopolysaccharides, Kashmir, Micrococcus yunnanensis, polyhydroxyalkanoates, Psychrobacter sp. AbstrakPolihidroksialkanoat (PHA) dan eksopolisakarida (EPS) adalah biopolimer yang diproduksi oleh bakteri yang hidup pada kondisi nutrisi yang terbatas. Dalam penelitian ini, strain bakteri diisolasi dari sumber air panas. Sampel tanah dikumpulkan dari Tatta Pani, Azad Kashmir, Pakistan. Strain bakteri AJ2 dan AJ3 dipilih karena kemampuannya menghasilkan PHA dan EPS. Analisis filogenetik menunjukkan bahwa strain AJ2 adalah Micrococcus yunnanensis dan AJ3 adalah Psychrobacter sp. Tiga sumber karbon (glukosa, gliserol, dan molase) digunakan untuk produksi polimer. pH tinggi (8) dan suhu tinggi (55 °C) diperiksa pengaruhnya terhadap produksi PHA dan EPS. Hasil tertinggi PHA diberikan oleh strain AJ3 (89,43%) dengan tetes tebu. Saat ditumbuhkan pada suhu 55 °C selama 24 jam, strain AJ3 menunjukkan akumulasi PHA tertinggi, 79% dengan glukosa. Pada pH basa 8, strain AJ3 memberikan 34% PHA dengan molase. Produksi EPS tertinggi diamati untuk strain AJ3. AJ3 menghasilkan 70g/L EPS dengan glukosa dan gliserol. Amplifikasi gen phaC dilakukan untuk mengkonfirmasi dasar genetik produksi PHA. Analisis FTIR menunjukkan pita yang jelas pada 1722 cm-1 dan 2925 cm-1 masing-masing mewakili gugus karbonil dan alkil PHA.Kata kunci: eksopolisakarida, Kashmir, Micrococcus yunnanensis, polihidroksialkanoat, Psychrobacter sp.